CULTURAL VALUE REPRESENTATION IN AVATAR: THE LAST AIRBENDER MOVIE POSTERS: MULTIMODAL DISCOURSE ANALYSIS - -, Rifda Faizatur Rahmah; Fitri Rakhmawati (Lire Journal (Journal of Linguistics and Literature), 2025)
This research aims to explore the representational meaning and cultural values depicted in Avatar: The Last Airbender 2024 movie posters through the lens of Multimodal Discourse Analysis and Halliday’s Systemic Functional Grammar. While previous studies on Avatar have focused on its philosophical themes, cultural representation, and narrative elements, by analyzing visual and textual elements in promotional materials, such as movie posters, in conveying cultural values, this gap will be address in this research. The study was chosen for its strong ties to East Asian cultural traditions, including philosophies, attire, and symbolic representations, making it a compelling subject for exploring cultural narratives in Hollywood media. A qualitative approach was employed, focusing on 7 posters selected from a total of 25, based on narrative representational aspects. Data were gathered from high-resolution movie posters on CineMaterial.com. Findings reveals that the posters embody East Asian cultural values such as harmony, resilience, and spiritual growth, conveyed through traditional attire, martial arts-inspired poses, and culturally significant backdrops. Textual elements like the phrase "Master Your Element" align with visual themes to emphasize personal growth and identity. The representational meaning highlights dynamic interactions among characters and their cultural contexts, offering insights into how multimodal texts function as cultural artifacts. This study concludes that the Avatar: The Last Airbender 2024 movie posters effectively combine visual and textual elements to represent East Asian cultural heritage while shaping narrative engagement, demonstrating how multimodal texts convey layered meanings by blending representational meaning with cultural values.